Faktor-Faktor Yang Berhubungan Dengan Kejadian Dermatitis Kontak Iritan Pada Pekerja Bagian Premix Di PT. X Cirebon - Irvan Ade Indrawan; Ari Suwondo; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Irritant contact dermatitis is a local non-immunologic inflammatory reaction of the skin caused by contact with exogenous or endogenous factors. This disease is characterized by inflammation of the polymorphic skin traits that have broad identification, such as: itching, redness, scaling, vesicles, and crusting papulovesikel. PT X is an industry which is engaged in the production of animal feed in Cirebon City. The production process is divided into several stages, weighing ingredients according to recipe, coarse crushing raw materials, mixing all the ingredients according to recipe, pellet forming and crumble establishment. Before mixing the main ingredient there was a process of weighing chemicals and feed supplement as prescribed in premix company section. The purpose of this research was to analyze the factors associated with the occurrence of irritant dermatitis contact in Premix workers in PT X Cirebon. The type of the research is an observational study with cross sectional approach. The subjects were 40 workers as part of Premix respondents. The results of the chi square test statistic obtained contact with the chemical (p value = 0.0001), years (p value = 1.000), duration of exposure (p value = 0.003), age (p value = 0.003), gender (p value = 0.017), knowledge (p value = 1.000), use of personal protective equipment (p value = 0.369), personal hygiene (p value = 0.689). The conclusion of this study is in contact with chemicals, long exposure, age and gender, associated with the incidence of irritant dermatitis contact. While working life, knowledge, use of personal protective equipment, and personal hygiene are not associated with the incidence of irritant contact dermatitis